2009
DOI: 10.1002/cmdc.200900069
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent, CNS‐Penetrant Orexin Receptor Antagonist Based on an N,N‐Disubstituted‐1,4‐diazepane Scaffold that Promotes Sleep in Rats

Abstract: Silent Night: Antagonism of the orexin (or hypocretin) system has recently been identified as a novel mechanism for the treatment of insomnia. Herein, we describe discovery of a dual (OX(1)R/OX(2)R) orexin receptor antagonist featuring a 1,4-diazepane central constraint that blocks orexin signaling in vivo. In telemetry-implanted rats, oral administration of this antagonist produced a decrease in wakefulness, while increasing REM and non-REM sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 12 publications
0
46
0
Order By: Relevance
“…The diazepane compound MK 4305 (33) with K i values of 0.55 and 0.35 nM at OX1-R and OX2-R [49,180,184] as well as a molecular weight of 450.19 g/mol has a log P of 4.24 and is included in a clinical phase III study. A volume distribution of 2.6 (rat) and 0.8 l/kg b. wt (dog) lets expect rather modest lipophilic properties.…”
Section: Non-peptide Ox-r Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diazepane compound MK 4305 (33) with K i values of 0.55 and 0.35 nM at OX1-R and OX2-R [49,180,184] as well as a molecular weight of 450.19 g/mol has a log P of 4.24 and is included in a clinical phase III study. A volume distribution of 2.6 (rat) and 0.8 l/kg b. wt (dog) lets expect rather modest lipophilic properties.…”
Section: Non-peptide Ox-r Ligandsmentioning
confidence: 99%
“…A volume distribution of 2.6 (rat) and 0.8 l/kg b. wt (dog) lets expect rather modest lipophilic properties. MK 4305 has been developed using 7-methyldiazepane and triazolyl-benzamide as core unit and is only one in a series of diazepanes highly potent as DORAs (see (34), (35) (Figure 7) [49,184].…”
Section: Non-peptide Ox-r Ligandsmentioning
confidence: 99%
“…This evidence therefore precludes the use of sleep-inducing agents under operational conditions in which individuals might be called upon to perform without impairment after taking the (13)(14)(15), impaired concentration and attention (16)(17)(18)(19), increased risk for accidents and injuries (20,21), worsened quality of life (22), increased aggression (23)(24)(25)(26), and increased use of alcohol (27,28). Several studies have also demonstrated that disturbed sleep is a potent risk factor for later onset development of major depression, panic disorder, alcohol, and substance abuse (27)(28)(29)(30). Therefore, an effective treatment for sleep disturbances that can be safely utilized in deployed military personnel in combat operations without performance-impairing effects has the potential for improving the success of combat operations, inoculating soldiers against battlefield stress-related psychiatric illnesses, and preserving the psychological health of the soldiers throughout the full deployment lifecycle.…”
Section: Rationalementioning
confidence: 99%
“…Therefore, more effective hypnotics are needed that facilitate sleep that is easily reversible in the event of an unexpected awakening that demands unimpaired cognitive and psychomotor performance. Recently, antagonism of the hypocretin (Hcrt; also called orexin) receptors has been identified as a target mechanism for the next generation of sleep medications (Brisbare-Roch et al, 2007;Dugovic et al, 2009;Whitman et al, 2009;Hoever et al, 2010Hoever et al, , 2012aColeman et al, 2012;Herring et al, 2012;Winrow et al, 2012;Betschart et al, 2013). The Hcrt system is well known to play an important role in the maintenance of wakefulness (de Lecea, 2012;Inutsuka and Yamanaka, 2013;Mieda and Sakurai, 2013;Saper, 2013).…”
Section: Introductionmentioning
confidence: 99%